Pola Kesalahan Siswa Pada Materi Peluang: Kajian Teori Newman Berdasarkan Gaya Kognitif - Ananda Wahyu Sailia Putri; Lusiana Prastiwi; Dedi Rahman Siolimbona (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
The high perception of difficulty in mathematics stems from its abstract nature, leading to a high rate of student errors. One factor influencing this is individual cognitive style. This study aims to examine students errors in solving probability problems using the Newman procedure from a cognitive style perspective. This study employs a descriptive qualitative approach. Data were collection through the GEFT test, a written probability test, and semi structured interviews. The research subjects consisted of two student from class XII-3 selected through purposive sampling based on following criteria: (1) into the field-independent or field-dependent category, (2) have a good comunication according to the teachers instructions. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that students with a field independent cognitive style made errors in transformation, process skills, and encoding. Meanwhile, students with a field dependent cognitive style made errors in comprehension, transformation, process skills, and encoding. These errors were caused by limited mastery of the material, low accuracy, and external influences. The result are expected to assist teachers in designing instructional strategies aligned with students cognitive style to reduce error in problem solving.Keywords: Newman Error Analysis, Probability, Cognitive Style